QPSK receiver outperforming the standard quantum limit for any signal power - Muller, Christian R.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
We present a quantum receiver for the discrimination of quadrature phase-shiftkeyed signals that approaches the Helstrom bound for any signal power. The discrimination isperformed via adaptive displacements prior to a single photon detector. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05